The association between life’s crucial 9 and all-cause, cancer-specific and cardiovascular mortality in US cancer survivors: a cohort study of NHANES - Hongyang Gong; Ming Gao; Zhiwen Zeng (BMC Cancer)
Abstract Background Life’s Crucial 9 (LC9) is a recently proposed cardiovascular health (CVH) scoring system that integrates psychological well-being with Life’s Essential 8 (LE8). However, its prognostic value remains unclear. This study aims to investigate the association between LC9 and outcomes among cancer survivors. Methods A total of 2,558 cancer survivors from the National Health and Nutrition Examination Survey (NHANES) 2005–2018 were included in this study. LC9, representing a dimension of psychological health, was calculated as the average of the LE8 score and the depression score. Cox proportional hazards regression, restricted cubic spline (RCS) analysis, subgroup analysis, and Kaplan-Meier survival curves were employed to evaluate the association between LC9 and mortality risk, with adjustments for potential confounders. Results During an average follow-up period of 80 months, 640 deaths occurred, including 205 from cancer and 128 from cardiovascular disease. After adjusting for all covariates using Cox regression, a 10-point increase in the LC9 score was associated with a 24% reduction in all-cause mortality (HR: 0.76; 95% CI: 0.68–0.84), a 19% reduction in cancer-specific mortality (HR: 0.81; 95% CI: 0.68–0.97), and a 28% reduction in cardiovascular mortality (HR: 0.72; 95% CI: 0.58–0.90). Kaplan-Meier survival curves indicated lower rates of all-cause, cancer-specific, and cardiovascular mortality among participants with higher LC9 scores. RCS analysis revealed a linear inverse association between LC9 and all-cause and cancer-specific mortality and a nonlinear inverse association with cardiovascular mortality. Conclusion Among cancer survivors in the United States, higher LC9 scores were independently associated with lower risks of all-cause, cancer-specific, and cardiovascular mortality. This finding highlights the potential link between cardiovascular health and survival outcomes in cancer survivors, suggesting that improving cardiovascular health may serve as an important preventive strategy to enhance survival rates in this population.